Mineralogical and Technological Evaluation of Saponites of the Uchtut Residential Place in the Republic of Uzbekistan - Umirov F.E., Fayzullaev N.I., Usanbayev N.Kh., Umirov U.F., Muzaffarov A.M., Pirnazarov F.G. (International Journal of Control and Automation, 2020)
Studied mineral composition of saponite in Uchtut, Navbahor, Navoi Region of Uzbekistan, district by chemical, X-ray diffraction, infrared spectroscopy Osprey -algebraic, differential – thermal analysis , as well as gamma-spectrometric analysis. It has been established that the main mineral in the residential place is saponite with a high content of magnesium and calcium , which is a mineral raw material for diversified use.